2015
DOI: 10.19030/jaese.v1i1.9104
|View full text |Cite
|
Sign up to set email alerts
|

A Study Of Undergraduate Students Alternative Conceptions Of Earths Interior Using Drawing Tasks

Abstract: Learning fundamental geoscience topics such as plate tectonics, earthquakes, and volcanoes requires students to develop a deep understanding of the conceptual models geologists use when describing the structure and dynamics of Earths interior. Despite the importance of these mental models underlying much of the undergraduate geoscience curriculum, surprisingly little research related to this complex idea exists in the discipline-based science education research literature. To better understand non-science-majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(23 reference statements)
0
1
0
7
Order By: Relevance
“…Using a two-group pre-test/post-test comparison study design, they found that 74% of 50 students who watched The Corea science fiction movies with questionable scientific accuracy held more misconceptions than 91% of 32 students who did not watch The Core as part of instruction. Even without the isolated influence of inaccurate science fiction movies, McAllister (2014) found that 22% of the 92 undergraduates she interviewed have no coherent conceptual model of Earth's interior that reflects current scientific understanding. In fact, only 9% of the 92 undergraduates could describe and sketch comprehensive conceptual models that were accurate.…”
Section: Ocean Floor Featuresmentioning
confidence: 95%
“…Using a two-group pre-test/post-test comparison study design, they found that 74% of 50 students who watched The Corea science fiction movies with questionable scientific accuracy held more misconceptions than 91% of 32 students who did not watch The Core as part of instruction. Even without the isolated influence of inaccurate science fiction movies, McAllister (2014) found that 22% of the 92 undergraduates she interviewed have no coherent conceptual model of Earth's interior that reflects current scientific understanding. In fact, only 9% of the 92 undergraduates could describe and sketch comprehensive conceptual models that were accurate.…”
Section: Ocean Floor Featuresmentioning
confidence: 95%
“…2,1 fogalomalkotási/ vernakuláris A 6. kérdésre adott válaszok és tanulói rajzok egy korosztályon átívelő tévképzete a Föld gömbhéjainak vízszintes rétegekben történő ábrázolása volt (10. ábra). Ez a tévképzet külföldi kutatásban is azonosított tévképzet (McAllister, 2004).…”
Section: 3 Fogalomalkotásiunclassified
“…Egy további, nagyobb arányban jellemző tévképzet, amely külföldi szakirodalmi adatokkal is összhangban áll (Barnett et al, 2006;Dahl et al, 2005;McAllister, 2004), amikor a Föld magjának anyagát lávaként vagy magmaként határozták meg, illetve itt is megjelent a földmag közvetlen összeköttetésének feltételezése a vulkánokkal (11. ábra).…”
Section: áBra 9 éVfolyamos Tanuló Fogalomalkotási Tévképzete a Föld unclassified
See 1 more Smart Citation
“…€bra 3. €vfolyamos tanul" prekoncepci"ja a hegys€gk€pződ€sről Egy tov•bbi, nagyobb ar•nyban jellemző t€vk€pzet volt, amely kˆlf‚ldi szakirodalmi adatokkal is ‚sszhangban van (Barnett et al, 2006;Dahl et al 2005, McAllister, 2004, amikor a F‚ld magj•nak anyag•t l•vak€nt vagy magmak€nt hat•rozt•k meg, illetve itt is megjelent a f‚ldmag k‚zvetlen ‚sszek‚ttet€s€nek felt€telez€se a vulk•nokkal (35. •bra).…”
Section: A Fƒld Belső Szerkezete ‚S Alapvető Folyamataiunclassified